2018
DOI: 10.1021/acs.jnatprod.8b00710
|View full text |Cite
|
Sign up to set email alerts
|

Bitter Taste Impact and Thermal Conversion of a Naringenin Glycoside from Cyclopia genistoides

Abstract: A naringenin derivative, isolated from Cyclopia genistoides, a bitter tasting herbal tea, especially when in green (unoxidized) form, was identified as (2S)-5-[α-L-rhamnopyranosyl-(1→2)-β-D-glucopyranosyloxy]naringenin (1). The compound partially epimerizes to (2R)-5-[α-L-rhamnopyranosyl-(1→2)-β-D-glucopyranosyloxy]naringenin (2) when heated at different temperatures (80, 90, 100, 110, and 120 °C) for a prolonged period in a phosphate buffer at pH 5. The fractional conversion model predicted the decrease in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Heating of the retentate reduced the concentration of most of the phenolic compounds, with 90 °C/4 h having a greater impact, in particular on mangiferin, isomangiferin, 2RNAR and 2SNAR (Table 2). Previous studies [39][40][41] provided insight into the relative heat stability of the compounds as determined by structure, as well as their likely degradation products. Alexander et al 9,31 demonstrated that mangiferin is a major contributor to the bitter taste of C. genistoides, that the ratio of mangiferin to isomangiferin might play a role, and that IDG and 2SNAR could suppress and enhance the bitter intensity of a xanthone fraction, respectively.…”
Section: Validationmentioning
confidence: 99%
“…Heating of the retentate reduced the concentration of most of the phenolic compounds, with 90 °C/4 h having a greater impact, in particular on mangiferin, isomangiferin, 2RNAR and 2SNAR (Table 2). Previous studies [39][40][41] provided insight into the relative heat stability of the compounds as determined by structure, as well as their likely degradation products. Alexander et al 9,31 demonstrated that mangiferin is a major contributor to the bitter taste of C. genistoides, that the ratio of mangiferin to isomangiferin might play a role, and that IDG and 2SNAR could suppress and enhance the bitter intensity of a xanthone fraction, respectively.…”
Section: Validationmentioning
confidence: 99%
“…Compounds O , Q and AD were tentatively identified as naringenin‐ O ‐(hexose‐ O ‐deoxyhexose) isomers due to the neutral loss of a hexose‐deoxyhexose [M − H − 162 − 146] − moiety 33 . Compounds O and Q were identified as (2 S )‐5‐ O ‐[α‐ l ‐rhamnopyranosyl‐(1 → 2)‐β‐ d ‐glucopyranosyl]naringenin and (2 R )‐5‐ O ‐[α‐ l ‐rhamnopyranosyl‐(1 → 2)‐β‐ d ‐glucopyranosyl]naringenin, respectively, based on their relative elution times in the first and second dimension and comparison of data to those of authentic reference standards 16,33,40 . Compound AD was identified as a related naringenin‐ O ‐(hexose‐ O ‐deoxyhexose) derivative, which showed identical MS behaviour to O and Q 33 …”
Section: Resultsmentioning
confidence: 99%
“…From Fraction D, compound 1 was identified as (2 S )‐5‐ O ‐[α‐ l ‐rhamnopyranosyl‐(1 → 2)‐β‐ d ‐glucopyranosyl]naringenin, previously isolated from Cyclopia genistoides. 16 From Fraction E, four compounds were identified as R ‐neo‐eriocitrin ( 2 ), 45,46 3‐ O ‐α‐ l ‐arabinopyranosyl‐3,4‐dihydroxybenzoic acid ( 5 ), 47 4‐ O ‐β‐ d ‐glucopyranosyl‐ Z ‐4‐hydroxycinnamic acid ( 6 ) 48 and 4‐(4′‐ O ‐β‐ d ‐glucopyranosyl‐4′‐hydroxy‐3′‐methoxyphenyl)‐2‐butanone ( 7 ) 49,50 . Compound structures are shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). These compounds exhibit various biological activities, [3][4][5][6][7] and the novel glycosides of flavones, [8][9][10][11][12] terpenes, [13][14][15][16][17] and steroids [18][19][20][21][22] are naturally occurring; therefore, they have attracted attentions of the pharmaceutical chemists. The synthesis of 2-O-α-L-rhamnosyl-β-O-glucosidic structure involves the rhamnosylation of 2-O in a glucosyl donor bearing an aglycon at the β-anomeric oxygen.…”
Section: Introductionmentioning
confidence: 99%